A virtuous circle: stakeholder perspectives of a short-term intensive parent training programme delivered within the context of routine services for autism in China - Fang, Z; Lachman, JM; Zhang, C; Qiao, D; Barlow, J (SAGE Publications, 2022)
Although the evidence of parent training programmes for families of autistic children has continued to grow, little is known about the experiences and perceptions of key stakeholders, especially in low- and middle-income countries. This qualitative study was part of a larger real-world evaluation of a short-term intensive parent training programme in routine services delivered to caregivers of autistic children aged 3–6 years in China. It aimed to provide insights into programme acceptability, reasons for participant involvement, and factors related to programme implementation. Fourteen caregivers participated in the in-depth interviews, and two focus group discussions were conducted with eight practitioners. Data were analysed using a combination of data- and theory-driven approaches. Findings point to the needs in low autism resource settings for substantial practice and feedback; group support; individualised coaching; more autism-related knowledge, resources and activities for children and extended family members; and organisational support to practitioners. Further research is suggested to address the recommendations and assess their effectiveness empirically.